Communication Directors and Public Relations Professionals in Public School Districts: A Literature Review (Journal of School Administration Research and Development, 2024)
A school district’s need to satisfy the school community’s expectations for current, accurate information and manage a social media presence has increased the necessity for superintendents to employ public relations professionals. As such, these professionals are a recent addition to many school districts’ administrative teams. However, few research studies were located that focused on public relations professionals or communication directors in public schools. The purpose of this literature review was to identify empirical studies and professional association resources that provided historical, contextual, and relevant information about communication directors in school districts. Based on the findings, we uncovered three themes related to the history, roles and responsibilities, and standards for public relations professionals. Such information can help practitioners support communication functions and help researchers identify needed lines of inquiry.